Perancangan dan Pembuatan Sistem Informasi Penilaian Pada SMK Bayu Pertiwi Sunggal - Marthin Yohannes Simanjuntak (PT. ALHAFI BERKAH INDONESIA, 2023)
The e-report application is an application for processing daily test scores, assignment scores, mid-semester examination scores and final semester examinations. Based on the author's observations while participating in the Educational Field Practice (PLK) in the 2020/2021 academic year at SMK Bayu Pertiwi Sunggal. At SMK Bayu Pertiwi Sunggal there are 7 majors, namely Building Modeling and Information Design, Construction and Property Business, Mechanical Engineering, Automotive Light Vehicle Engineering, Motorcycle Engineering and Business, Computer Network Engineering, and Fisheries and Freshwater Agribusiness. The value processing information system built at SMK Bayu is web-based using the Laravel framework, component-based PHP programming that has high performance for large-scale web application development. In the information system that has been built, there are 4 access rights, namely admin, principal, subject teacher, and homeroom teacher.